Implications of dollarization for Belize - Ford, Emory ([CCMS] [St. Augustine]TT, 2001)
Examines the experiences of selected dollarized countries to see if any lessons can be drawn from them. Focuses on Belize's macro-environment over the 1990 to 2000 period. Looks at the potential benefits and costs to Belize of proceeding along this path.